CD158a+/CD158b+ NK cell imbalance correlates with hypertension in patients with pre‐eclampsia. (14th March 2022) - Xu, Xiuxiu; Zhao, Xirui; Chen, Ling; Liu, Muziying; Hu, Ziming; Ke, Jieqi; Fu, Binqing; Zhou, Yonggang; Wei, Haiming
Abstract: Problem: Preeclampsia, a pregnancy complication with hypertension and proteinuria, seriously threats the health and lives of the mother and the baby. The pathogenesis of pre‐eclampsia remains incompletely understood. The role of peripheral natural killer cells (NK cells) in the pre‐eclampsia is unclear. Method of study: Flow cytometry was performed to detect the expression of CD158a (KIR2DL1) and CD158b (KIR2DL2/3) in peripheral NK cells of healthy pregnant women (HP) and patients with pre‐eclampsia (PE). Differentially expressed genes (DEGs) in CD158a + and CD158b + NK cells were identified by RNA‐sequencing and real‐time PCR. Protein array analysis was used to identify altered protein levels in the serum of study participants. Results: CD158a + NK cell numbers were increased in the peripheral blood of patients while the number of CD158b + NK cells was reduced. In addition, the percentage of CD158a + NK cells within the peripheral NK subset was positively correlated with systolic blood pressure while the percentage of CD158b + NK cells was negatively correlated with systolic blood pressure. RNA‐seq and real‐time PCR showed that the expression of ERAP2 and GCH1, the genes that regulate blood pressure and angiogenesis, was decreased in CD158a + compared to CD158b + NK cells. Consistently, the level of proteins involved in angiogenesis was altered in the serum of pre‐eclampsia patients compared to healthy individuals. Conclusions: CD158a + NK cells increased while CD158b + NK cells decreased in the peripheral blood of patients with pre‐eclampsia compared to healthy individuals. The change in the frequency of CD158a + /CD158b + NK cells is related to the increase in blood pressure.